Lagged rejuvenation of groundwater indicates internal flow structures and hydrological connectivity. Issue 10 (6th April 2020) - Kolbe, Tamara; Marçais, Jean; de Dreuzy, Jean‐Raynald; Labasque, Thierry; Bishop, Kevin
Abstract: Large proportions of rainwater and snowmelt infiltrate into the subsurface before contributing to stream flow and stream water quality. Subsurface flow dynamics steer the transport and transformation of contaminants, carbon, weathering products and other biogeochemistry. The distribution of groundwater ages with depth is a key feature of these flow dynamics. Predicting these ages are a strong test of hypotheses about subsurface structures and time‐varying processes. Chlorofluorocarbon (CFC)‐based groundwater ages revealed an unexpected groundwater age stratification in a 0.47 km 2 forested catchment called Svartberget in northern Sweden. An overall groundwater age stratification, representative for the Svartberget site, was derived by measuring CFCs from nine different wells with depths of 2–18 m close to the stream network. Immediately below the water table, CFC‐based groundwater ages of already 30 years that increased with depth were found. Using complementary groundwater flow models, we could reproduce the observed groundwater age stratification and show that the 30 year lag in rejuvenation comes from return flow of groundwater at a subsurface discharge zone that evolves along the interface between two soil types. By comparing the observed groundwater age stratification with a simple analytical approximation, we show that the observed lag in rejuvenation can be a powerful indicator of the extent and structure of the subsurface discharge zone, while the vertical gradient of the age‐depth‐relationship can still be used as a proxy of the overall aquifer recharge even when sampled in the discharge zone. The single age stratification profile measured in the discharge zone, close to the aquifer outlet, can reveal the main structure of the groundwater flow pattern from recharge to discharge. This groundwater flow pattern provides information on the participation of groundwater in the hydrological cycle and indicates the lower boundary of hydrological connectivity. Abstract : Measured groundwater ages at several locations downslope in different depths yield a single overall groundwater age stratification representative for the catchment. The groundwater age stratification reveals a subsurface discharge zone. By applying a simple analytical approximation, two‐measure can be extracted: (1) The extent of the subsurface discharge zone in relation to the recharge zone and (2) the overall recharge volume.